Perspectives of Tacloban City's administrative agencies and public market vendor leaders on the financial returns of green packaging - Albert, Brianna Jade C.; Antuine, Aizhyl Khie C.; Bunga, Maxine Yvonne P.; Labnao, Ethyl Joy
On January 1, 2024, Tacloban City implemented Ordinance No. 2023-15-06 to reduce plastic bags and polystyrene packaging, offering a nine-month grace period for existing plastic inventory disposal. Urging public market vendors to adopt, this qualitative study assesses the perceived positive financial returns of transitioning to green packaging. Utilizing a qualitative narrative research design, the study captures detailed perspectives from the interview of the 15 key informants-nine from administrative agencies and six market section leaders. The City Environment and Natural Resources Office focuses on environmental policies; the Local Economic Development and Investment Promotion Office discusses economic trends; the City Planning and Development Office informs urban sustainability strategies; the City Local Market Administration offers market implications; the City Council clarifies ordinance objectives; and the City Collector's Office reveals financial benefits for vendors. Thematic and narrative analyses delineate insights, which are then inductively consolidated into a comprehensive framework through cross-sectional analysis grounded on the Triple Bottom Line theory (environmental, social, and economic). Results show clear financial returns across dimensions, with environmental and social benefits implying economic advantages-ranging from cost savings to increased vendor income-illustrating a cycle of benefits. However, constraints from vendors' perspectives highlight the knowledge gap between adopters and implementers of the ordinance, particularly in the social aspect. Hence, enhanced collaborative efforts among stakeholders are crucial for effectively communicating the long-term financial returns of adopting green packaging. By addressing constraints and leveraging advantages, stakeholders can maximize the economic, social, and environmental benefits of green packaging in Tacloban City's public market.